A Comparison of The Health Impacts of Individual Level and Area Based Welsh Government Fuel Poverty Schemes - Sian Morrison-Rees; Sarah Lowe (International Journal of Population Data Science, 2020)
Introduction Living in a cold and/or damp house is known to increase the risk of morbidity, mortality and excess winter deaths. To reduce fuel poverty in Wales, the Welsh Government developed schemes to provide energy efficiency improvements to those most likely affected by fuel poverty.